2018
DOI: 10.1155/2018/1671072
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin Therapy Administered Early after Narcolepsy Type 1 Onset in Three Patients Evaluated by Clinical and Polysomnographic Follow-Up

Abstract: Narcolepsy type 1 is a rare disabling sleep disorder mainly characterized by excessive daytime sleepiness and cataplexy, an emotion-triggered sudden loss of muscle tone. Patients have a selective degeneration of hypocretin-producing neurons in the dorsolateral posterior hypothalamus with growing evidence supporting the hypothesis of an autoimmune mechanism. Few case studies that reported intravenous immunoglobulin therapy (IVIg) suggest the efficacy of IVIg when administered early after disease onset, but the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Only a few investigators [39,[90][91][92] have tried IVIG in early-onset narcoleptic patients to understand its therapeutic efficacy, but the results are controversial due to the small sample size, openlabel design, and self-report observations. The results suggest a potential improvement in frequency and severity of cataplexy and ameliorated daytime sleepiness, data further confirmed by new evidence [93]. Given the possibility of spontaneous improvement of cataplexy [94], more controlled studies are indicated.…”
Section: Immunotherapymentioning
confidence: 59%
“…Only a few investigators [39,[90][91][92] have tried IVIG in early-onset narcoleptic patients to understand its therapeutic efficacy, but the results are controversial due to the small sample size, openlabel design, and self-report observations. The results suggest a potential improvement in frequency and severity of cataplexy and ameliorated daytime sleepiness, data further confirmed by new evidence [93]. Given the possibility of spontaneous improvement of cataplexy [94], more controlled studies are indicated.…”
Section: Immunotherapymentioning
confidence: 59%
“…To date, the results have been controversial due to the small sample size, open label design, and self-reported observations. However, an improvement in cataplexy frequency and severity, as well as in EDS, was reported, but further data are required to exclude the possibility of a spontaneous improvement in NT1 symptoms during the disease course [ 88 ]. Overall, despite some promising results, further studies should address the role of immunotherapy in NT1 [ 89 ].…”
Section: Immunotherapymentioning
confidence: 99%
“…In adult cases, headache, sometimes associated with stiff neck 101 or rise in CSF leukocytes, 89 was the most common complaint, whereas one patient presented a not better-defined allergic reaction. 83 In children, side effects included infectious episodes (a flu-like syndrome and viral gastroenteritis), 78 skin reactions with urticaria and petechiae, 80 hypotension and nausea, 90 headache, fever, and flushing 70 requiring therapy withdrawal. Although until now no serious adverse events occurred in NT1 patients treated with monoclonal antibodies, these drugs have potentially lethal side effects, ie, severe infusion-related reactions, secondary autoimmunity 94 and lifethreatening infections secondary to immunosuppression, in particular progressive multifocal leukoencephalopathy (PML).…”
Section: Side Effects Of Immunotherapymentioning
confidence: 99%
“… 77 In three other cases treated within 1–4 months from symptoms’ onset mixed effects were observed, with some improvement of EDS, and in two cases also of cataplexy, although no significant changes of polysomnographic parameters were documented. 78 A 16-year-old girl with NT1 and severe bizarre hallucinations, with an inflammatory CSF (positive oligoclonal bands and pleocytosis) and undetectable hcrt-1 levels at the baseline examination, was treated with IVIG and showed only a transient improvement of the hallucinations. Interestingly, the CSF pleocytosis gradually disappeared after treatment, but CFS hcrt-1 levels remained unchanged.…”
Section: Immunotherapiesmentioning
confidence: 99%
See 1 more Smart Citation